Incidence of new-onset diabetes among sudanese renal transplant patients using different immunosuppressive regimens: A retrospective study - Alaa Mohammedazeem Elzain; Safaa Badi; Bashir Alsiddig Yousef; Habab Khalid Elkheir (CHRISMED Journal of Health and Research, 2021)
Background: New onset diabetes after renal transplant (NODAT) is a serious complication of therapy with immunosuppressive drugs. The aim of this study was to estimate the incidence of NODAT and its association with immunosuppressant regimens within 6 months of the administration. Methodology: A descriptive retrospective case finding hospital-based study, conducted in the department of nephrology at Ahmed Gasim Hospital from January to September 2017, on patients who underwent renal transplantation between June 2015 and June 2016. The data were collected using a structured checklist. The collected data were analyzed by the Statistical Package for Social Sciences (SPSS). Results: A total of 110 patients were included, the majority of studied patients were males (71.8%) and in the age group of 20–40 years (50.9%). The most commonly prescribed immunosuppressant regimen was regimen, which consists of methylprednisolone as induction therapy and tacrolimus + azathioprine + prednisolone as maintenance therapy. Regarding the adverse effects, 11 (10%) of them developed NODAT throughout 6 months after transplantation. However, no significant association was found between the postulated risk factors and the incidence of NODAT. Conclusion: The incidence of NODAT was 10% throughout 6 months after transplantation. Correlations between sociodemographic characteristics, immunosuppressant regimens, episodes of rejection with the incidence of NODAT were found statistically insignificant.